Increasing the bearing capacity of ethanol as a component of alternative motor fuel: experiments and molecular modeling - Bozhko, Ye. O.; Yesylevskyy, S. O.; Cherniavskyi, Ye. K.; Sheludko, Ye. V.; Piljavsky, V. S.; Polunkin, Ye. V.; Bogomolov, Yu. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
A Schiff base containing fragments of D-glucose and benzoic acid is synthesized. It is shown that the introduction of this additive into ethyl alcohol — alternative fuels component — significantly (1.7–3.6 times) increases its bearing capacity. The effect of additives on the structure formation in ethanol is studied by the method of complete atomic classical molecular dynamics. Adding the additive to ethanol increases the mixture density and decreases the diffusion coefficient of ethanol. Structuring occurs due to the formation of complexes stabilized by hydrogen bonds, which consist of an additive molecule surrounded by a shell of ∼37 oriented ethanol molecules. Moreover, metastable dimers and trimers of an additive molecule are formed with a lifetime of about 0.5 ns.